Technical ability of force application as a determinant factor of sprint performance - Morin, J.-B.; Edouard, P.; Samozino, P. (Medicine & Science in Sports & Exercise, 2011)
Purpose: We transposed the concept of effectiveness of force application used in pedaling mechanics to calculate the ratio of forces (RF) during sprint running and tested the hypothesis that field sprint performance was related to the technical ability to produce high amounts of net positive horizontal force. This ability represents how effectively the total force developed by the lower limbs is applied onto the ground, despite increasing speed during the acceleration phase.